ALBUMIN TO GLOBULIN RATIO AND ITS ASSOCIATION WITH LIVER ENZYMES IN ALCOHOLIC LIVER DISEASE - Pandeya, Arun; Tamang, Jagatman; Dhungana, Arun; Kafle, Rita (Journal of Chitwan Medical College, 2024)
Background: High alcohol consumption may lead to alcoholic liver disease, the diagnosis of which is made by using clinical laboratory tests among which liver enzymes, De Ritis ratio, and Albumin to Globulin ratio are more reliable. The main aim of this study was to evaluate the albumin to globulin ratio and its correlation with the liver enzyme panel in patients with alcoholic liver disease. Methods: A prospective cross-sectional study was conducted among the patients visiting the hospital from November 2022 to September 2023 after getting ethical approval. Non-probability sampling method and convenience sampling technique was used for enrolling the participants in this study. After performing specific biochemical tests, results are expressed as mean ± standard deviation for continuous data. In addition, Pearson correlation coefficient was used to measure the correlation of albumin to globulin ratio with liver enzymes. Results: Liver enzymes, such as AST and ALT were significantly raised in patients with alcoholic liver disease. A rise in AST activity was greater than that of ALT activity resulting in a ratio of AST to ALT (De Ritis ratio) greater than two but a ratio of serum albumin to globulin is lesser than one in more than two-thirds (67.60%) of the patients and the ratio of serum albumin to globulin is negatively correlated with liver enzymes. Conclusions: The albumin to globulin ratio is decreased in the majority of alcoholic liver disease patients. Therefore, along with De Ritis ratio, the albumin to globulin ratio can be used as a marker for alcoholic liver disease.